First case report on Bickerstaff brainstem encephalitis in a young adult from Syria: Bridging clinical knowledge and practice - Ahmad Almohamed; Ayham Qatza; Haifa Alsamman; Suaad Hamsho; Mohammad Atia; Rahaf tamer; Almaya Mhd Ali; Waddah Kazkz (Radiology Case Reports)
Bickerstaff Brainstem Encephalitis (BBE) is a rare immunologic condition characterized by CNS inflammation, presenting with ataxia, external ophthalmoplegia, altered consciousness, and quadriplegia. A 25-year-old male with no significant medical history exhibited symptoms of blurred vision, diplopia, facial numbness, and imbalance following a respiratory infection. Brain MRI revealed hyperintense lesions in the cerebral peduncle and pons on T2-weighted/FLAIR sequences but not on T1-weighted sequences, indicative of demyelination. Lumbar puncture showed clear cerebrospinal fluid with lymphocytic pleocytosis (80 cells/μl, 95% lymphocytes) and normal protein levels. The patient was treated with intravenous methylprednisolone (1000 mg/day for five days), resulting in recovery and normal follow-up MRI findings. Early diagnosis and treatment are crucial to minimize complications and improve outcomes. Additionally, airway management is essential for patients with impaired respiratory function, and long-term rehabilitation may be necessary for those recovering from encephalitis.